Choosing a major in the age of digital influence: a comparative study of Generation Z in Kazakhstan and Italy - Grechi, Daniele; Mardenova, Leila K.; Yessimzhanova, Saira (Frontiers in Education, 2025)
The choice of a university major significantly impacts students’ professional trajectories. Despite its importance, limited research compares the factors influencing major choice among students in different cultural contexts, such as Italy and Kazakhstan. This study explores the primary motivations influencing Generation Z students’ selection of academic majors in these countries. Utilizing a survey administered to approximately 800 respondents in Italy and Kazakhstan, the research examines factors including perceived academic experience value, financial incentives, social proof and influence networks, intellectual motivations, the perceived impact of digital marketing tools, and the impact of the COVID-19 pandemic. The findings provide insights into the similarities and differences in decision-making processes among students in these countries, contributing to a deeper understanding of how cultural, economic, and marketing factors shape educational choices.